Effect of Sodium Bicarbonate and Acetic Acid on Hibiscus Macrophyllus Seed-Borne Fungal Pathogens, Seed Germination, and Seedling Growth - Tati Suharti; NFN Danu; Y.M.M Anita Nugraheni (Jurnal Perbenihan Tanaman Hutan, 2020)
Hibiscus macrophyllus, an important tropical tree, has high economic potential, however there are the problems in seedling procurement, i.e. seed dormancy and seed-borne pathogen. The purpose of the research was to evaluate the effect of sodium bicarbonate and acetic acid on fungal colonization, seed germination, and seedling growth of H. macrophyllus. A completely randomized design was used to test the six treatments: untreated seed, soaking seeds in boiling water and left 24 hours, soaking in boiling water and left 24 hours followed by soaking in acetic acid 1% (15 minutes), soaking in boiling water and left 24 hours followed by soaking in sodium bicarbonate 5% (15 minutes), soaking in acetic acid 1% (15 minutes) followed by soaking in boiling water and left 24 hours, soaking in sodium bicarbonate 5% (15 minutes) followed by soaking in boiling water and left 24 hours. Soaking in sodium bicarbonate 5% (15 minutes) followed by soaking in boiling water and left 24 hours could significantly decrease the fungal colonization. Sodium bicarbonate 5% and acetic acid 1% treatments could not improve seed germination. The sodium bicarbonate treatment followed by soaking in boiling water increased the seedling diameter, leaf length, leaf wide, root length, and leaf number.